If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(7 + -3x) + 5 = 2x + 10 x + (7 * -1 + -3x * -1) + 5 = 2x + 10 x + (-7 + 3x) + 5 = 2x + 10 Reorder the terms: -7 + 5 + x + 3x = 2x + 10 Combine like terms: -7 + 5 = -2 -2 + x + 3x = 2x + 10 Combine like terms: x + 3x = 4x -2 + 4x = 2x + 10 Reorder the terms: -2 + 4x = 10 + 2x Solving -2 + 4x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 4x + -2x = 10 + 2x + -2x Combine like terms: 4x + -2x = 2x -2 + 2x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 2x = 10 + 0 -2 + 2x = 10 Add '2' to each side of the equation. -2 + 2 + 2x = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 10 + 2 2x = 10 + 2 Combine like terms: 10 + 2 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 3x+17+5=7x+10 | | 2/3q-2=1/3q+7 | | -45+n=44 | | B+4=-1b | | x^3+x^2+2x-20=0 | | 6(1X+3)=24 | | 0.5(P+8)=q | | f(x)=15-1 | | 2m+2n-5= | | 4x+32=20x | | 3x+1=-3x+31 | | ln(x^2)=9 | | -5/8+83/8= | | 4p+8-3p= | | 750+8=758 | | 28=(3x+4)*4 | | 4x+-2=2(x+-6) | | 3(2x+5)=ax+5 | | 4(5x+2)-6x=5(2x+4) | | 60X=0.1 | | 6(8+x)=78 | | 4x-6x=2x | | 9(2n-5)=(9n+7)+8 | | 61x^2+56x+4=0 | | -2x+4=4x+16 | | (x-15)(x+3)=0 | | 7(12+y)=4 | | 3t+10=16 | | 3/5n-10=2/5n | | -42=4v-8 | | 5/x-3/5=20 | | 6x+5+7x=34 |